META ANALYSIS OF THE INFLUENCE OF INQUIRY LEARNING MODEL ON STUDENT LEARNING OUTCOMES IN PHYSICS AND JUNIOR HIGH SCHOOL SUBJECTS - Vinika Humaira; Wahyuni Satria Dewi (PILLAR OF PHYSICS EDUCATION, 2022)
Education is an effective way to increase the quality of human resources; as a guide for implementing national education, curriculum is one of the most essential variables that can influence the learning process' performance. Graduate competency is one of the educational criteria, and it may be attained by employing the appropriate learning model in the teaching and learning process. One of the inquiry learning models is the most often utilized learning paradigm. The goal of this study is to determine the amount of the effect size of the inquiry model's influence on high school and junior high school physics results. A meta-analysis was used in this study.. Meta-analysis is a type of study that involves summarizing, examining, and analyzing data from a number of previous studies. Conducting a literature review, gathering data, examining, assessing, analyzing, and interpreting articles, and preparing report results are all stages of meta-analysis research. The statistical data must be included in the criteria for the articles used. There are two research findings that may be deduced from the data analysis results. First, as can be seen from the summary effect size values for high school 0.42 and junior high school 0.41, the influence of the inquiry learning model on learning outcomes is stronger at the high school level than at the junior high school level. The two summary effect sizes influence the inquiry learning model the most influence on the subject matter, namely the vibration and wave material of 0.73 and the lowest on the motion system material of 0.15.